Mentor teachers’ and student teachers’ perspectives toward teacher leadership - Rania Sawalhi (15375493) (2021)
The current study adopted the Teacher Leadership Inventory (TLI) to understand the perceptions of mentor teachers and student teachers towards teacher leadership, and identify the variables which affected these perspectives. A one-way ANOVA was used to determine whether there were any statistically significant differences between their perceptions on the four factors of the TLI, as well as several demographic variables. Findings revealed that mentor teachers had significantly higher scores than student teachers on two factors; Shared Expertise and Shared Leadership. Further, the demographic variables of years of experience, nationality, and gender affected the mentor teachers’ perceptions towards the three factors of Shared Leadership, Supra-Practitioner and Principal Selection respectively. While years of experience affected the student teachers’ perspectives towards the Principal Selection factor. Therefore, these differences should be taken into consideration by teacher education institutions, mentor teachers, and school principals, specifically during the student teachers’ practicum experiences. Other Information Published in: Mentoring & Tutoring: Partnership in Learning License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13611267.2021.1899586